Revitalisasi Ekonomi Kerakyatan Melalui Perkembangan Media Online Shop - Sari, Ulia; Adila, Citra (IAINU Kebumen, 2024)
This study focuses on the revitalization of the people's economy through the development of online shop media and analyzes the obstacles and challenges of online shop media platforms to the growth of small and medium enterprises. The research method includes literature studies and data analysis related to the development of online shop media to the people's economy. The results show that online shop businesses empower individuals to become independent entrepreneurs. They can manage their own businesses and have control over their economic future. However, there are also obstacles and challenges in online shop media to the people's economy. Therefore, it is necessary to improve understanding, regulation, and empowerment in order to maximize the benefits of online shop media in supporting the growth of the people's economy.